Berpikir Dalam Perspektif Psikologi dan Islam - Moh Harits Amanda Rifqi (Program Studi Psikologi Islam, 2023)
This article includes a discussion of the ability to think in the perspective of Psychology and Islam, written to fulfill the study of discussing the ability to think broadly through aspects of the psychological and Islamic perspective, articles made using descriptive qualitative methods with literature study techniques through library sources and previous articles as material for discussion and data acquisition, and from the results of studies on thinking in the perspective of psychology and Islam. Thinking is defined as the process of reason and thought which is the most noble gift given by Allah SWT to humans and thinking is also known as a mental process. In general, thinking can be distinguished between natural thought and scientific thought. Natural thinking is a theoretical model based on everyday life under the influence of nature and its environment.